Kemampuan Penggunaan Media Pembelajaran Digital Oleh Orang Tua Sebagai Sarana Pendukung Belajar Anak Tingkat PAUD Di Desa Bektiharjo Tahun 2022 - Agus Fathoni Prasetyo; Nur Hamidah (Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
Abstract: Based on the background of the problem, this study provides answers to the formulation of the problem (1) What is the ability of parents to use digital learning media as a means of supporting early childhood learning through digital parenting training media? (2) What are the efforts to improve parents' digital literacy skills in using digital learning media?. With the aim of (1) to determine the ability of parents to use digital learning media (2) to improve the ability of parents to use digital learning media. This research method is descriptive qualitative with field study, and the data that has been collected is obtained from the results of interviews, observations, test instruments, and documentation. Then, to find out valid data, researchers used source triangulation and method triangulation. The results of the study concluded that the digital literacy abilities of parents in using digital learning media as a means of supporting children's learning at the PAUD level through digital parenting training media in Bektiharjo village in 2022 were carried out smoothly and well and there was a lot of knowledge that was unknown until they found out.